Ectomesenchymal Six1 controls mandibular skeleton formation - Luo, Songyuan; Liu, Zhixu; Bian, Qian; Wang, Xudong (Frontiers in Genetics, 2023)
Craniofacial development requires intricate cooperation between multiple transcription factors and signaling pathways. Six1 is a critical transcription factor regulating craniofacial development. However, the exact function of Six1 during craniofacial development remains elusive. In this study, we investigated the role of Six1 in mandible development using a Six1 knockout mouse model (Six1-/-) and a cranial neural crest-specific, Six1 conditional knockout mouse model (Six1f/f; Wnt1-Cre). The Six1-/- mice exhibited multiple craniofacial deformities, including severe microsomia, high-arched palate, and uvula deformity. Notably, the Six1f/f; Wnt1-Cre mice recapitulate the microsomia phenotype of Six1-/- mice, thus demonstrating that the expression of Six1 in ectomesenchyme is critical for mandible development. We further showed that the knockout of Six1 led to abnormal expression of osteogenic genes within the mandible. Moreover, the knockdown of Six1 in C3H10 T1/2 cells reduced their osteogenic capacity in vitro. Using RNA-seq, we showed that both the loss of Six1 in the E18.5 mandible and Six1 knockdown in C3H10 T1/2 led to the dysregulation of genes involved in embryonic skeletal development. In particular, we showed that Six1 binds to the promoter of Bmp4, Fat4, Fgf18, and Fgfr2, and promotes their transcription. Collectively, our results suggest that Six1 plays a critical role in regulating mandibular skeleton formation during mouse embryogenesis.